2014
DOI: 10.2147/ott.s62781
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A (-197G/A) and IL-17F (7488T/C) gene polymorphisms and cancer risk in Asian population: a meta-analysis

Abstract: Interleukin (IL)-17 has been shown to play an important role in the pathogenesis of inflammation and cancer. The IL-17A (-197G/A) and IL-17F (7488T/C) polymorphisms have been extensively investigated with cancer risk, but individually published results have been inconclusive. The aim of this study was to clarify the effects of the IL-17A (-197G/A) and IL-17F (7488T/C) polymorphisms on cancer risk in Asian populations. Relevant studies were identified by searching databases extensively. The association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Taken together, despite some limitations, the present meta-analysis provided a more precise estimation of the relationship between the IL-17 gene SNPs and gastric cancer risk compared with the individual studies, which also supports the previous findings (Dai et al, 2014). Furthermore, other possible causative variants in the IL-17 gene should be explored.…”
Section: Discussionsupporting
confidence: 88%
“…Taken together, despite some limitations, the present meta-analysis provided a more precise estimation of the relationship between the IL-17 gene SNPs and gastric cancer risk compared with the individual studies, which also supports the previous findings (Dai et al, 2014). Furthermore, other possible causative variants in the IL-17 gene should be explored.…”
Section: Discussionsupporting
confidence: 88%
“…IL-17A and IL-17F are the most important members; they all located at 6q12 and comprise three exons and two introns (Iwakura et al, 2011). Previous studies have shown that over-expression of IL-17A and IL-17F contributes to the development of various cancers, such as pancreatic, gastric, and lung cancers (Cully, 2014;Dai et al, 2014;Zarogoulidis et al, 2014;Kaabachi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“… 4 In addition, several previous meta-analyses have evaluated a specific gene polymorphism and risk for all cancer types, respectively. 5 7 …”
Section: Introductionmentioning
confidence: 99%